Strategik Kepala Sekolah Mengimplementasikan Pembelajaran Kokurikuler Kurikulum Merdeka pada Sekolah Menengah Atas Samarinda - Agustina Pitriyani; Zaenab Hanim (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2023)
“Merdeka Curriculum” co-curricular learning is new learning for the world of education, so all strategies are needed in implementing it. This research aims to explore the principal's strategy in implementing “merdeka curriculum” co-curricular learning at Samarinda High School. This research uses a qualitative approach with a case study type of research. Three key informants were involved in collecting data for this research, namely, principal, deputy principal for curriculum, and teachers. Data collection uses observation, interviews, and documentation methods. The data analysis process is carried out through the stages of reduction, presentation and drawing conclusions. The research results show that the school principal's strategy in implementing “merdeka curriculum” co-curricular learning begins with facilitating teachers to take part in “merdeka curriculum” mentoring and training, exploring students' needs to carry out learning in the Strengthening Pancasila Student Profile Project (P5), and enriching P5 learning materials for students. The school principal's strategy in implementing “merdeka curriculum” co-curricular learning can bring about change and improvement in the character of students through the application of the six dimensions of the Pancasila student profile.